International corporate finance : value creation with currency derivatives in global capital markets / Laurent L Jacque - Jacque, Laurent L.
International Corporate Finance offers thorough coverage of the international monetary system, international financing, foreign exchange risk management and cross-border valuation. Additionally, the book offers keen insight on how disintermediation, deregulation and securitization are re-shaping global capital markets.